HIV pathogenesis in the female genital tract during chronic HIV infection : the impact of inflammation, T cell memory differentiation status and homeostatic cytokines on mucosal T cell immunity - Gumbi, Pamela (Division of Virology, 2014)
Includes bibliographical references (leaves 124-150).